The Jurisprudence Of Product Liability In Nigeria: A Need To Complement The Existing Fault Theory - Akinrinmade, Gbade (Journal of Sustainable Development Law and Policy, 2025)
This article argues for the adoption of strict liability principle as an additional theoretical basis of liability, to complement the existing fault theory on product liability claims in Nigeria. The fault theory, which currently is the only theoretical basis of liability, unduly burdens claimants. The reason for this is that such claimants are expected to establish fault despite the lack of insight into the complex processes of production. While establishing fault in cases of manufacturing defect may seem less onerous, it is an uphill task when it concerns design or warning defects. Bearing in mind that a principal rationale of tort law is to ensure that prejudiced parties are compensated for losses suffered, this article explains why it is necessary to assess and review applicable principle of liability in Nigeria to ensure that it is in line with the demands of justice, which should be in conformity with the peculiar circumstances of its operating environment.